2020
DOI: 10.1080/03091902.2020.1831633
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D printing-based probe for impedance spectroscopic examination of oral mucosa: design and preliminary testing with phantom models

Abstract: The diagnosis of oral potentially malignant disorders currently relies on histopathological examination of surgically removed biopsies causing pain and discomfort for the patient. We hypothesise that non-invasive bioimpedance spectroscopy (BIS) method would overcome these problems and could make possible regular screening of at-risk patients. Previously several handmade probes have been introduced in such BIS studies. However, for the first time, we aimed to design a 3D printed probe and test it with model sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In our previous studies, we found that designing a successful 3D printed probe for BIS measurements is a challenging task [3], and we faced similar challenges in this study. Selecting proper electrode materials for the newly designed probes was crucial (table 1).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our previous studies, we found that designing a successful 3D printed probe for BIS measurements is a challenging task [3], and we faced similar challenges in this study. Selecting proper electrode materials for the newly designed probes was crucial (table 1).…”
Section: Discussionmentioning
confidence: 77%
“…In BIS, a weak alternating current is injected through a sample, e.g. human tissue, and, as an outcome, the impedance magnitude and phase are determined for each frequency point [3]. There has been an abundance of research and implementation of the BIS technique to various biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such elastomers can be modified or synthesized to demonstrate self-healing properties or good skin adhesion [147], [148]. Printing methods commonly used include inkjet [149], [150], screen [151], stencil, molding [140], [141] and extrusion-based (that we have been exploring in our Centre due to their simplicity) [152]- [154] and other 3D printing technologies [155], [156], as well as roll-to-roll contact printing approaches, such as gravure, flexographic printing [11] and transfer printing methods. Another interesting and very promising approach that we have been exploring is laserinduced graphitization of polyimide films and the transfer of the conductive structures on elastomers [157]- [159].…”
Section: Recent Advancements In Bioimpedance Sensor Realizationmentioning
confidence: 99%